A cement pier anchor for culture in net cage - TANG CHAO; CHEN SHENGBING; LONG XIA; LIU JIEQUN; ZHOU YANLING (2016)
The utility model discloses a cement pier anchor for culture in net cage, include heavy the sticking together of cement that wholly is " ten " word cross coupling and describes, the heavy last end face centre who sticks together of cement is equipped with the main ring and turns round, and the end face centre of heavy transverse beam that sticks together of cement and longitudinal recording is equipped with the secondary ring and turns round, and the heavy transverse beam that sticks together of cement, the bottom surface width of longitudinal recording are greater than the width of top surface. The utility model discloses structural design is novel, and under the heavy same volume's that sticks together of cement condition, the heavy shape that sticks together of cement has the characteristics that the inertia couple is great, the focus is lower, has bigger antidumping ability, can improve the anchor power of cement pier anchor. 本实用新型公开了一种用于网箱养殖的水泥墩锚，包括整体呈"十"字交叉梁状的水泥沉坨，水泥沉坨的上端面中心设有主环扭，水泥沉坨的横向梁和纵向梁的端面中心设有次环扭，